Pyramiding of leaf rust resistance genes in bread wheat variety DWR 162 through marker assisted backcrossing - Yadawad, Arati; Gadpale, Anil; Hanchinal, R. R.; Nadaf, H. L.; Desai, S. A.; Biradar, Suma; Naik, V. Rudra (The Indian Journal of Genetics and Plant Breeding, 2017)
A popular widely grown but leaf rust susceptible Indian bread wheat variety was pyramided with two leaf rust resistance genes, Lr24 and Lr28 by Marker Assisted Backcrossing (MABC). The near isogenic line of PBW 343 introgressed with Lr24 and Lr28 was used as a donor. The MABC approach employed one SSR marker, Xwmc313 and one SCAR marker SCS421 with its locus linked to Lr28 and two SCAR markers, SCS719 and SCS 1302 linked to Lr24 for foreground selection to select plants carrying Lr24 and Lr28 genes. Marker assisted background selection in BC2F2to recover the genome of recipient parent involving 42 polymorphic SSR markers dispersed throughout the genome facilitated mean recurrent parent genome (RPG) recovery of 80.3% with a range from 67.5-94.7%. BC2F2 plants were characterized for DUS (Distinctiveness Uniformity Stability) for phenotypic identification of plants that mostly resemble DWR 162 variety. Field evaluation of BC2F2 plants for yield and its component traits to assess the effect of these two genes in the background of DWR 162 revealed high yield potential of selected plants along with leaf rust resistance and no yield penalty was apparent. This study successfully demonstrate the practical utility of MABC in wheat rust resistance breeding for developing resistant lines in the background of any elite and popular wheat cultivar with relatively higher speed and precision.